Reflections on Ten Years of USAID’s Experience with Political Economy Analysis and Thinking and Working Politically - and Brinkerhoff, Derick; Cassidy, Marc (TWP CoP, 2023)
The global Thinking and Working Politically (TWP) Community of Practice (CoP), the Washington DC TWP CoP, and USAID organised a webinar on 5 December 2022 to take stock of how USAID and its partners have used PEA to inform programme strategy, design and implementation, and support TWP. This paper synthesises the key points arising from the webinar, including observations on the impacts, opportunities, challenges, and prospects for PEA/TWP to become more deeply adopted and sustained as a development methodology and approach across sectors. It starts by defining key concepts. It then highlights insights from the discussions of the impact of the application of PEA and TWP principles across sectors. The paper concludes by looking at progress achieved to date, as well as constraints and opportunities to increase the uptake of both thinking and working politically in USAID-sponsored programming.